The Role of Pharmaceutical Scientists in the Formation of a Healthy Lifestyle as a Value Orientation - Larisa Galiy; Tetiana Lutaieva; Larysa Lenchyk; Oleksandr Surikov; Svitlana Moroz (MDPI AG, 2022)
This article focuses on the role pharmaceutical scientists play in achieving social well-being, in particular in the formation of a healthy lifestyle as a value orientation among students and the public in historical retrospect. The following set of research methods was used: a general scientific method, and a historical (chronological, logico-historical, retrospective), personalized, empirical method (including the questioning of pharmaceutical interns and the analytical processing of questionnaires). The territorial boundaries of the study cover Slobozhanshchyna, a historical and geographical region centered in Kharkiv. The educational activities of Slobozhanshchyna's pharmaceutical scientists during the 19th and early-20th centuries, as well as in the modern period, are presented. Attention is drawn to the fact that the role of pharmaceutical scientists in forming the environment for the development of a harmonious, spiritually and physically developed personality in historical retrospect is important. It is noted that the founders of pharmaceutical education in Ukraine initiated educational activity as a means for promoting the formation of a healthy lifestyle in the educational space and outside of the Imperial Kharkov University. The changes in the public and educational activities recommended for forming a healthy lifestyle among Slobozhanshchyna's medical scientists and naturalists during the Imperial era have been generalized. The analysis of the research sources and questionnaires of pharmaceutical interns allowed us to assert that, in modern times, Slobozhanshchyna's pharmaceutical scientists are trying to organize socially useful activities, taking into account the best achievements of the founders of pharmaceutical education in Ukraine. The "orientation to a healthy lifestyle of representatives of the institution of higher pharmaceutical education" has been proposed. This includes the adoption of a set of material, social, and spiritual benefits and ideals considered to be objects of purpose in the pursuit of a healthy lifestyle by employees and students (i.e., part of the implementation of the mission of the University), and using these as tools to meet the needs of both university representatives and ordinary citizens. This article contains a number of factors that mediated the formation of a healthy lifestyle as a value orientation of an individual, including: (a) the circumstances of the individual's life (the conditions of education of the individual); (b) the individual's consciousness reflecting the general and specific conditions of their personality formation; (c) the motivation of the real behavior mediated by the subject's activities. The presence of these factors was identified as typical for the health-saving educational environment. This article provides recommendations regarding the following measures for the organization and effective promotion of a healthy lifestyle by modern pharmaceutical scientists: provide an opportunity to study the peculiarities of the organization of educational activities by scientists of the past to students and specialists in the pharmaceutical field; open museum expositions devoted to the problem of healthcare; conduct master class lectures and educational events devoted to the problem of forming a comprehensively developed personality; involve students in joint research on the problem of active longevity; provide informational support to educators and the public through scientific and popular science publications; conduct awareness-raising work with the population in order to create a health-saving environment.